Stabilitas Fisikokimia dan Sifat Antipenuaan Kulit Formula Krim Berbahan Aktif Alami (Physicochemical stabilities and Skin Antiaging Properties of Bioaktive-based Cream Formulas) - Rita K Sari; Nyoman J Wistara; Deded S Nawawi; Nopen Meisaroh; Ietje Wientarsih; D R Agungpriyono; L N Sutardi; Mawar Subangkit; Vetnizah Juniantito (Masyarakat Peneliti Kayu Indonesia, 2017)
The purpose of this study was to analyze the physicochemical stabilities and in vivo antiaging properties of the cream formulas of F1, F2, and F3 which contained the active compound of 0.1% 0.18, and 0.36%, respectively. The active compound was the combination of ethyl acetate fraction of Toona sinensis, Centella asiatica, and Acacia mangium leaf (1:2:1). For physicochemical stability tests (color, odor, acidity, and antioxidant activity), the creams were stored for 21 days in the refrigerator, room temperature, and extreme temperature (±40 ⁰C). For in vivo antiaging test, the mice skin were smeared with cream and UV irradiated for 15 minutes per day. After two and four weeks, the mice skins were biopsied. The results showed that the physicochemical properties of creams stored in the refrigerator were stable. The storage of creams at room and extreme temperature decreased the physicochemical properties. The application of cream formulas on mice skin after two to four weeks were able to increase the thickness of epidermis, but has not been able to increase the collagen skin of mice.Keywords: Acacia mangium, Centella asiatica, ethyl acetate fraction of leaf, physicochemical and antiaging properties of cream, Toona sinensis